Analisis Implementasi Akad Musyarakah Mutanaqisah pada Pembiayaan ASN di Bank NTB Syariah Cabang Sriwijaya - Muslihun; Sanurdi; Kasry A. Rahman (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Musyarakah Mutanaqishah is a form of cooperation between two or more parties for the ownership of an item or asset. Where this cooperation will reduce the ownership rights of one party while the other party increases its ownership rights, this transfer of ownership is through a payment mechanism for other ownership rights. This research aims to explain the implementation of the Musyarakah Mutanaqisah contract in ASN financing at Bank NTB Syariah Sriwijaya Branch and the obstacles in implementing the contract. The method used is descriptive qualitative by observing, evaluating, analyzing and describing the phenomena that occur in implementing the Musyarakah Mutanaqisah contract on ASN financing at Bank NTB Syariah Sriwijaya Branch. The results of the study state that the implementation of the Musyarakah Mutanaqisah (MMQ) contract for ASN consumer financing at Bank NTB Syariah Sriwijaya Branch has been carried out by the DSN-MUI fatwa as stated in the SOP for financing implementation. The obstacles faced by Bank NTB Syariah in the implementation of ASN financing with the MMQ contract include, among others, the lack of understanding of customers regarding the regulations and mechanisms for implementing financing with the Musyarakah Mutanqisah (MMQ) contract; some customers cannot provide proof of asset ownership on behalf of the customer or their spouse, some customers apply for financing without bringing their spouse for various reasons, and some customers are unable to provide funds for administrative and insurance costs required before the financing disbursement process can be carried out.